2016
DOI: 10.5539/ijel.v6n7p36
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of French (L3) Wh-question by Persian (L1) Learners of English (L2) as a Foreign Language: Optimality Theory

Abstract: Recent decade has been prominent in investigating third language acquisition (L3). This study presents an Optimality theoretic account of French wh-question by learners whose first and second language are Persian and English respectively. Additionally, it investigates transfer at the initial stage based on the three dominant transfer hypotheses namely, L1 transfer hypothesis, L2 status factor, Cumulative Enhancement Model (CEM) in the domain of L3 acquisition. First, in French and Persian wh-question structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This may be attributed to the immediate access to information about lexical crossover, but information about overlaps in syntactic structure requires a deeper knowledge of the L3 (Rothman, 2013; Westergaard, 2021b). This finding was compatible with similarity‐driven models of L3 acquisition (Flynn et al., 2004; Rothman, 2011, 2015; Slabakova, 2017; Westergaard, 2021a), as opposed to accounts that have argued for a default L1 or L2 effect (e.g., Bardel & Falk, 2007; Bayona, 2009; Berends et al., 2017; Falk & Bardel, 2011; Hermas, 2010, 2015; Mollaie et al., 2016; Na Ranong & Leung, 2009; Park, 2016). Our results did not support the idea of wholesale transfer at the initial state as proposed by Rothman (2011), nor did the findings support the idea of wholesale transfer taking place as soon as the parser detects similarity between the L3 and one of the previously acquired languages (at the initial stages) based on the four‐way hierarchy of Rothman (2013, 2015)—lexicon, phonology, morphology, syntax.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This may be attributed to the immediate access to information about lexical crossover, but information about overlaps in syntactic structure requires a deeper knowledge of the L3 (Rothman, 2013; Westergaard, 2021b). This finding was compatible with similarity‐driven models of L3 acquisition (Flynn et al., 2004; Rothman, 2011, 2015; Slabakova, 2017; Westergaard, 2021a), as opposed to accounts that have argued for a default L1 or L2 effect (e.g., Bardel & Falk, 2007; Bayona, 2009; Berends et al., 2017; Falk & Bardel, 2011; Hermas, 2010, 2015; Mollaie et al., 2016; Na Ranong & Leung, 2009; Park, 2016). Our results did not support the idea of wholesale transfer at the initial state as proposed by Rothman (2011), nor did the findings support the idea of wholesale transfer taking place as soon as the parser detects similarity between the L3 and one of the previously acquired languages (at the initial stages) based on the four‐way hierarchy of Rothman (2013, 2015)—lexicon, phonology, morphology, syntax.…”
Section: Discussionsupporting
confidence: 76%
“…The rejection of H 0 is incompatible with a default explanation of crosslinguistic influence in L3 acquisition as previous studies have suggested (e.g., Bardel & Falk, 2007;Bayona, 2009;Berends et al, 2017;Falk & Bardel, 2011;Hermas, 2010Hermas, , 2015Mollaie et al, 2016;Na Ranong & Leung, 2009;Park, 2016). A L1 or L2 default would predict that bilingual speakers of the same language combination should behave similarly regardless of the nature of the L3, a conclusion that is not compatible with the results of our experiment.…”
Section: The Effect Of Lexiconmentioning
confidence: 75%
See 1 more Smart Citation